Identification and appraisement of the main pollution sources of Vilcanota river in the Calca - Urubamba sector - Taipe Bolaños, Miguel (2006)
Vilcanota River’s Valley is one of the most important rivers in the Cusco Region, within the sector comprised between Calca and Urubamba Provinces, an area with a large population where countryside and city live along together, and with a huge tourist stream. One of the main concerns is the increasing of pollution in Vilcanota River’s waters, since the river is the only place where all waste water coming from all towns along this valley flow into, including the City of Cusco itself, thus this river is a very important water source for agricultural activities, human consumption and amusement. For this reason, the study «Identification and Appraisement of the Main Pollution Sources of Vilcanota River in the Calca-Urubamba Sector» is presented, which will comprehend environmental, physical, biological and social issues, river’s waters characteristics, and the identification of the main pollution sources, and so on.